Assessment of Renal Injury in Patients Undergoing Elective EVAR Using Urinary Neutrophil Gelatin-Associated Lipocalin, Interleukin 18, and Retinol-Binding Protein. (July 2017) - Noorani, Ayesha; Sadat, Umar; Rollins, Katherine E.; Chowdhury, Mohammed M.; Tang, Tjun Y.; Harrison, Seamus C.; Usman, Ammara; Burling, Keith; Nordon, Anthony; Boyle, Jonathan R.
Acute kidney injury (AKI) is a recognized complication post-endovascular aneurysm repair (EVAR). Neutrophil gelatin-associated lipocalin (NGAL), interleukin 18 (IL-18), and retinol-binding protein are emerging urinary biomarkers that have shown promise in detecting subclinical and clinical renal impairment. In this study, we assessed changes in these urinary biomarkers as well as serum creatinine (SCr) in patients undergoing EVAR. Urine samples were collected prospectively at 5 time points for each recruited patient: pre-EVAR (baseline) and 6, 12, 24, and 48 hours after the procedure for serial assessment of urinary biomarkers. Serum creatinine was quantified preoperatively and at 24 and 48 hours postoperatively. Serial changes of urinary biomarkers and SCr were assessed. A significant increase in NGAL and IL-18 from baseline was observed ( P < .05), as early as 6 hours for NGAL. A significant rise in levels of NGAL and IL-18 precedes the significant rise in SCr. These findings highlight the potential of emerging urinary biomarkers in detecting early AKI following EVAR.